Исследование динамики поведения корпуса МТ-ЛБ при стрельбе - Васильев, Антон Юрьевич; Пономарев, Е. П.; Бруль, С. Т. (НТУ "ХПИ", 2006)
Розв'язана задача розробки методики багатоваріантного аналізу напружено-деформованого стану корпусу МТ-ЛБ при проведенні модернізації шляхом встановлення більш потужних модулів озброєння. Вибрані раціональні параметри варіювання для вирішення вказаної задачі.

The methods of multiple strain-stress state analysis of the MT-LB hull during conducting of modernization by establishment of more powerful armament modules are developed. Efficient parameters for varying for the decision of the indicated task are chosen.
Keywords: корпус боевой машины; метод конечных элементов; боевой модуль; напряженно-деформированное состояние; расчетно-экспериментальный метод; орудия